SYTUACJA EKONOMICZNO-FINANSOWA POPEGEEROWSKICH GOSPODARSTW ROLNYCH W WIELKO POLSCE I W POLSCE - Czyżewski, A.; Grzelak, A.; Jankowiak, J. (Wydział Prawa i Administracji UAM, 1999)
The main aim of this study was to evaluate economic situation of the ex-state farms in Wielkopolska Region and in Poland. In the article used are the results of research conducted by the Authors and by the Institute of Agriculture and Food Industry Economics. The paper includes four parts. The first one presented range of the research and the methodology adopted. The second part includes analysis of the production factors in studied farms. The subject of the next chapter was economic situation in restructured units. The last part is a resumé. The main thesis of this article is the statement that ex-state farms in Wielkopolska have reached relative more profitable economic results than other such farms in the country. Moreover it is pointed that the future development units created on the base of the state farms is dependable except on insiding circumstances also on macroeconomic factors what was reflected in worsening profitability of these farms in 1997 during a recession in agriculture.
ECONOMIC SITUATION OF THE EX-STATE FARMS IN WIELKOPOLSKA REGION AND IN POLAND